RNA Binding Protein OsTZF7 Traffics Between the Nucleus and Processing Bodies/Stress Granules and Positively Regulates Drought Stress in Rice - Guo, Chiming; Chen, Lingli; Cui, Yuchao; Tang, Ming; Guo, Ying; Yi, Yin; Li, Yan; Liu, Liqing; Chen, Liang (Frontiers in Plant Science, 2022)
Tandem CCCH zinc finger (TZF) proteins are essential components of processing bodies (PBs) and stress granules (SGs), which play critical roles in growth development and stress response in both animals and plants through post-transcriptional regulation of target mRNA. Here, we characterize the biological and molecular functions of a novel tandem zinc finger protein, OsTZF7. The expression of OsTZF7 was up-regulated by abiotic stresses, including polyethylene glycol (PEG) 4000, NaCl, and abscisic acid (ABA) in rice. Accordingly, overexpression of OsTZF7 increased drought tolerance and enhanced sensitivity to exogenous ABA in rice, whereas knock-down of OsTZF7 resulted in the opposite phenotype. RNA-seq analysis revealed that genes related to “response to stress”, “abscisic acid signaling”, “methylated histone binding” and “cytoplasmic mRNA processing body” are regulated by OsTZF7. We demonstrated that OsTZF7 can traffic between the nucleus and PBs/SGs, and the leucine-rich nuclear export signal (NES) mediates the nuclear export of OsTZF7. Additionally, we revealed that OsTZF7 can bind ARE or ARE-like motifs within the 3’ untranslated region of down-regulated mRNAs, and interact with PWWP family proteins in vitro. Together, these results indicate that OsTZF7 positively regulates drought response in rice via ABA signaling, and may be involved in mRNA turnover.